But every thing yields the same result!

Geometry Level 4

In \triangle A B C ABC , B = 2 C \angle B=2\angle C and D D is a point on B C BC such that A D AD bisects B A C \angle BAC and A B = C D AB=CD Then find the measure of B A C \angle BAC .


The answer is 72.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
May 16, 2015

Let C = θ \angle C = \theta , then B = 2 θ \space \angle B = 2\theta , B A C = A = 18 0 3 θ \space \angle BAC = \angle A = 180^\circ - 3\theta , D A B = D A C = 9 0 3 θ 2 \space \angle DAB = \angle DAC = 90^\circ - \dfrac {3\theta}{2}\space and B D A = 18 0 9 0 + 3 θ 2 2 θ = 9 0 θ 2 \angle BDA = 180^\circ - 90^\circ + \dfrac {3\theta}{2} - 2\theta = 90^\circ - \dfrac {\theta}{2} .

Using Sine Rule, we have:

C D A D = sin ( 9 0 3 θ 2 ) sin θ \dfrac {CD}{AD} =\dfrac {\sin{\left(90^\circ - \frac {3\theta}{2}\right)}}{\sin{\theta}} \space and A B A D = sin ( 9 0 θ 2 ) sin 2 θ \space \dfrac {AB}{AD} =\dfrac {\sin{\left(90^\circ - \frac {\theta}{2}\right)}}{\sin{2\theta}} .

Since A B = C D \space AB = CD ,

sin ( 9 0 3 θ 2 ) sin θ = sin ( 9 0 θ 2 ) sin 2 θ cos 3 θ 2 sin θ = cos θ 2 sin 2 θ cos 3 θ 2 = cos θ 2 2 cos θ 2 cos θ cos 3 θ 2 = cos θ 2 2 cos θ ( 4 cos 3 θ 2 3 cos θ 2 ) = cos θ 2 2 cos θ ( 4 cos 2 θ 2 3 ) = 1 2 cos θ ( 2 cos θ 1 ) = 1 4 cos 2 θ 2 cos θ 1 = 0 cos θ = { 1 + 5 4 θ = 3 6 1 5 4 θ = 10 8 unacceptable \begin{aligned} \Rightarrow \dfrac {\sin{\left(90^\circ - \frac {3\theta}{2}\right)}}{\sin{\theta}} & = \dfrac {\sin{\left(90^\circ - \frac {\theta}{2}\right)}}{\sin{2\theta}} \\ \dfrac {\cos{\frac {3\theta}{2}}}{\sin{\theta}} & = \dfrac {\cos{\frac {\theta}{2}}}{\sin{2\theta}} \\ \cos{\frac {3\theta}{2}} & = \dfrac {\cos{\frac {\theta}{2}}}{2\cos{\theta}} \\ 2\cos{\theta}\cos{\frac {3\theta}{2}} & = \cos{\frac {\theta}{2}} \\ 2\cos{\theta} \left(4\cos^3{\frac {\theta}{2}} - 3\cos{\frac {\theta}{2}} \right) & = \cos{\frac {\theta}{2}} \\ 2\cos{\theta} \left(4\cos^2{\frac {\theta}{2}} - 3 \right) & = 1 \\ 2\cos{\theta} \left(2\cos{\theta} -1 \right) & = 1 \\ 4\cos^2{\theta} - 2\cos{\theta} -1 & = 0 \\ \Rightarrow \cos{\theta} & = \begin{cases} \frac{1+\sqrt{5}}{4} & \Rightarrow \theta = 36^\circ \\ \frac {1- \sqrt{5}}{4} & \Rightarrow \theta = 108^\circ \quad \text{unacceptable} \end{cases} \end{aligned}

Therefore, B A C = 18 0 3 θ = 18 0 3 × 3 6 = 7 2 \space \angle BAC = 180^\circ - 3\theta = 180^\circ - 3\times 36^\circ = \boxed{72^\circ}

Ahmad Saad
Dec 11, 2016

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...